Assessment of the Effect of Beef and Mutton Meat Prices on Chicken Meat Prices in Turkey Using Different Regression Models and the Decision Tree Algorithm - Akin, Ahmet Cumhur; Arikan, Mehmet Saltuk; Cevrimli, Mustafa Bahadir; Tekindal, Mustafa Agah (Kafkas Univ, Veteriner Fakultesi Dergisi, 2020)
Determination of the extent to which increases in the price of red meat is reflected in the price of chicken meat will shed light to the sector in many areas, including production planning. The purpose of this study is to present how the increases in the price of red meat are reflected in the consumer prices of chicken meat and to determine the estimation rate of the consumer prices of chicken meat by analysing the monthly average consumer prices of chicken meat, beef and mutton (TRY/kg) in Turkey between January 2005 and September 2018 using different regression models and the decision tree algorithm. The results of the study indicate that in predicting the prices of chicken meat using the prices of beef, the cubic regression equation gives accurate predictions at a rate of 91.4%, and in predicting the prices of chicken meat using the prices of mutton, the cubic regression equation gives accurate predictions at a rate of 89.9%. It was estimated that 1% increase in the prices of beef would result in an increase by 1.35% in the prices of chicken meat, and a 1% increase in the prices of mutton would result in an increase by 0.39% in the prices of chicken meat.
Türkiye’de dana ve koyun eti fiyatlarının tavuk eti fiyatlarına etki düzeylerinin farklı regresyon modelleri ve karar ağacı algoritması ile değerlendirilmesi
Keywords: Red meat; Chicken meat; Price; Regression; Turkey